2000
DOI: 10.1177/073724770002500302
|View full text |Cite
|
Sign up to set email alerts
|

Reading Assessment and Instructional Practices in Special Education

Abstract: This study analyzed the instructional reading methods and reading assessment practices employed by K-12 special education teachers. Eight hundred special education teachers from four Midwestern states were surveyed regarding the frequency of use and usefulness of standardized and informal reading assessment practices and the frequency with which they used various reading instructional techniques. Responses were analyzed to determine percent of teachers employing each technique and the mean rating of usefulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Although the WARP passages are not curriculum-based measures in the strong sense of CBM, they do sample the broader curricular domain of reading. As Arthaud, Vasa and Steckelberg (2000) put it, CBM uses "materials drawn from the students' curriculum, or materials of comparable dif culty that are similar to the curricular materials used in daily instruction" (p. 206-7).…”
Section: Introductionmentioning
confidence: 99%
“…Although the WARP passages are not curriculum-based measures in the strong sense of CBM, they do sample the broader curricular domain of reading. As Arthaud, Vasa and Steckelberg (2000) put it, CBM uses "materials drawn from the students' curriculum, or materials of comparable dif culty that are similar to the curricular materials used in daily instruction" (p. 206-7).…”
Section: Introductionmentioning
confidence: 99%
“…As Denton (1999) reported, teachers can use test results of either formal or informal assessment to monitor a student's reading skills. The formal assessments include state-mandated standardized tests for monitoring reading progress, while the informal assessments include school-district or school-wide tests, curriculum-based tests, and teacher-strategic alternatives for ongoing performance assessment (Arthaud, Vasa & Steckelberg, 2000;Campbell, 2001;Denton, 1999;Rueda & Garcia, 1994. Curriculum-based reading tests include vocabulary tests, 'end of unit basal tests,' 'skills continua' and 'end of the book basal tests' to name a few (Arthaud, et al, 2000;Rueda & Garcia, 1994).…”
Section: How Are Potential Reading Problems Identified?mentioning
confidence: 99%
“…The formal assessments include state-mandated standardized tests for monitoring reading progress, while the informal assessments include school-district or school-wide tests, curriculum-based tests, and teacher-strategic alternatives for ongoing performance assessment (Arthaud, Vasa & Steckelberg, 2000;Campbell, 2001;Denton, 1999;Rueda & Garcia, 1994. Curriculum-based reading tests include vocabulary tests, 'end of unit basal tests,' 'skills continua' and 'end of the book basal tests' to name a few (Arthaud, et al, 2000;Rueda & Garcia, 1994). Teacher-strategic alternatives include, but are not limited to interviews with students, parents or previous teachers, ongoing observations, teacher-crafted questionnaires, text discussions, analyses of writing samples or journals, and monitoring of oral reading (Arthaud, et al, 2000;Rueda & Garcia, 1994.…”
Section: How Are Potential Reading Problems Identified?mentioning
confidence: 99%
See 1 more Smart Citation
“…Many special education assessment textbooks also identify IRIs as viable tools for evaluating reading skills in students who are referred for special education services or who receive special education services (McLoughlin & Lewis, 2005;Overton, 2003;Taylor, 2003). Indeed, a survey of special educators in four states revealed that special educators are just as likely to use IRIs as they are to use another widely recommended technique, curriculum-based measurement (CBM) of oral reading fluency (Arthaud, Vasa, & Steckelberg, 2000).…”
mentioning
confidence: 99%